Correlation of specific absorption rates in the human head due to multiple independent sources, Loughborough Antennas & Propagation Conference, Loughborough, 16th - 17th November 2009 - Whittow, W.; Panagamuwa, C.; Derat, B.; Morrow, Ivor L. (Cranfield University, 2009)
This paper examines how the SAR in the head is combined when exposed to the field due to multiple sources. The mechanisms when the sources have the same and different frequencies are discussed. FDTD simulation results are included when an anatomically realistic head is excited by various sources including: plane waves, vertically and horizontally orientated dipoles positioned in front and by the side of the head. Results are presented for two sources over the frequency range 0.5 to 4GHz.
Loughborough Antennas & Propagation Conference, Loughborough, 16th - 17th November 2009